Optimizing the Performance of the Satintelkam Society Unit in Safeguarding Labor Protests in the Legal Territory of the Sidoarjo Police - Septiandari, Lora (Advances in Police Science Research Journal, 2024)
The focus of the research in this final assignment is Optimizing the Performance of the Satintelkam, Social and Cultural Unit in Securing Demonstrations in the Legal Area of ​​the Sidoarjo Police. This research was conducted because there was chaos during the demonstration by workers. The aim of conducting research is to: (1). Describe the performance of the Satintelkam Social and Cultural Unit in securing labor demonstrations in the jurisdiction of the Sidoarjo Police, (2). Describe the factors that influence the performance of the Satintelkam Social and Cultural Unit in securing labor demonstrations in the jurisdiction of the Sidoarjo Police, (3). Describe efforts to optimize the performance of the Satintelkam Social and Cultural Unit in securing labor demonstrations in the jurisdiction of the Sidoarjo Police. The concepts used in this research are the performance concept, optimization concept, demonstration concept, MOPI and intelligence concept. The theories used as analytical tools in this research are management theory, competency theory and SWOT analysis. The method used in this research is a qualitative method. The data sources used in this research are primary data sources and secondary data sources. And this research uses data analysis using triangulation. The findings from the implementation of this research are: (1) The performance of the Satintelkam Social and Cultural Unit in securing demonstrations has not been optimal (2) the implementation of the performance of the Social and Cultural Unit is influenced by several factors, namely: (a) lack of personnel; (b) lack of infrastructure; (c) lack of coordination between agencies; (d) labor union figures who are difficult to communicate with. The conclusions from the research are: (1) the performance of the Satintelkam Social and Cultural Unit is not optimal (2) the performance of the Satintelkam Social and Cultural Unit is influenced by several factors (3) improving the quality of performance through Management Theory and Competency Theory.